Odpowiedzi

2010-02-20T20:30:08+01:00
A).... = pierwiastek 3.stopnia + 2*pier.3.st. * 1 +1 ^3=3 +2 pierw.3.st.z 3 + 1 = 2 pierw. 3. stopnia z 3 +4

....= 3^3 - 2*3* 2 pierw. z 2 + (2pierw. z2)^3= 9-12 pierw.z 2 + 16=25-12 pierw. z 2

....=(2 pierw.z3)^3 +2*2pierw3*1+1^3=25+4pierw. z 3

wszedzie gdzie jest napisane pierw. z... chodzi on pierwiastek trzeciego stopnia :)
2010-02-20T20:35:57+01:00
A)(∛3+1)³=(∛3)³+3(∛3)²*1+3*∛3*1²+1³ =3+3(∛3)²+3(∛3)+1= =4+3(∛3)²+3(∛3)
(3-2∛2)³=3³+3*3²*2∛2+3*3*2∛3+(2∛2)³=9+27*2∛2+9*2∛3+16=25+36∛3
(2∛3+1)³=(2∛3)³+3*(2∛3)²*1+3*2∛3*1²+1³=24+3*(2∛3)²+3*2∛3+2=
=26+3*(2∛3)²+3*2∛3
b) (∛3+∛2)(∛9-∛6+∛4)=(∛3)³+(∛2)³=3+2=5
(∛5-2)(∛25+2∛5+4)=(∛5)³-2³=5-8=-3